PENINGKATAN MINAT BELAJAR DAN KREATIVITAS MELALUI PROJECT BASED LEARNING PADA SISWA KELAS V SDN SARIHARJO - Bonifatius Sigit Yuniharto; Siti Rochmiyati (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This study aims to see whether the Project-Based Learning model can be used by fifth grade students at SDN Sariharjo to increase their interest in learning and creativity. An important part of this Classroom Action Research is the planning and implementation of the research itself. This study involved sixteen people. Methods such as direct observation, questionnaires, and documentation were used to collect data. This study uses quantitative and qualitative data analysis methods. In the Project-Based Learning model, the syntax (1) defines the basic question/problem; (2) designing project plans; (3) set the schedule; (4) monitor student and project progress; (5) assess the results; (6) evaluating experiences and reflections can increase students' interest in learning and creativity. The Project Based Learning model has a positive influence on the interest and creativity of 10 students (62.50 percent) and 8 students (50.00 percent) in the early stages of implementation. More than half of the students had a high interest in learning, and seven students had a creative disposition after the first cycle of action. Fourteen students (87.5 percent) in the second cycle showed a high level of interest and encouragement in their learning, and eight of these students ( 50.00 percent) included in the creative category.